Consumo de combustível de um trator agrícola no preparo do solo para a cultura do algodão irrigado em função da pressão de inflação nos pneus - Montanha, Gustavo Kimura; Guerra, Saulo Philipe Sebastião; Andrade-Sanchez, Pedro; Campos, Fernando Henrique [UNESP]; Lanças, Kléber Pereira [UNESP] (EIA Energy in Agriculture, 2011)
Currently, the efficiency in field operations and the increased productivity of crops is only possible with the use of agricultural machinery and equipment. This intensification of mechanized activities in agriculture, however, led to higher energy costs on farms mainly in the fuel consumption of agricultural tractors. The objective was to compare the fuel consumption of a tractor on tillage operations for irrigated cotton in semi-arid region varying two tire inflation pressures. The tests were conducted in Maricopa Agricultural Center (MAC), an experimental farm belonging to The University of Arizona using a 4x2 TDA Case tractor equipped with a 88kw autopilot system. The results showed lower values in the hourly fuel consumption by using the minimum tire inflation pressure of 124 kPa for all tillage equipment used.

Atualmente a eficiência nas operações de campo e o aumento na produtividade das culturas só são possíveis com o uso de máquinas e equipamentos agrícolas. Essa intensificação de atividades mecanizadas na agricultura, contudo, acarretou maiores gastos energéticos nas propriedades rurais principalmente no consumo de combustível dos tratores agrícolas. O objetivo do trabalho foi comparar o consumo de combustível de um trator agrícola no preparo do solo na cultura do algodão irrigado em região semi-árida variando-se duas pressões de inflação nos pneus. Os ensaios foram realizados na Maricopa Agricultural Center (MAC), fazenda experimental pertencente à The University of Arizona utilizando um trator Case 4x2 TDA de 88kW equipado com sistema de piloto automático. Os resultados evidenciaram menores valores no consumo horário de combustível utilizando a menor pressão de inflação de 124 kPa para todos os equipamentos de preparo de solo utilizados.
Fuel consumption of an agricultural tractor on tillage operations for irrigated cotton as function of tire inflation pressure
Keywords: Test; Mechanization; Precision agriculture; Ensaio de máquinas; Mecanização agrícola; Agricultura de precisão